Revolution & Cinema - Ribas, Daniel; Crespo, Nuno; Gray, Ros; Givanni, June; Silva, Aldones; Cardoso, Eduardo Prado; Gil, Isabel Capeloa; Duarte, João Oliveira; Mason, Matthew; Uras, Riccardo (UCP Press, 2025)
In this volume we gathered the contributions of various researchers that aim to address the relationship between cinema and revolution. The book opens with a conversation between Ros Gray, specialist in militant filmmaking, particularly in relation to liberation struggles and revolutionary movements in Mozambique, Angola, Guinea-Bissau and Burkina Faso, and June Givanni, film curator, archivist, international consultant around Pan-African cinema and founding director of the June Givanni Pan-African Cinema Archive (JGPACA). This volume also gathers contributions by: Aldones Silva on the work of the Brazilian visual artist Marcela Cantuária; Eduardo Prado Cardoso and his reading of the film Malunguinho directed by Felipe Peres Calheiros; Isabel Capeloa Gil on colonial memories of Portuguese cinema; João Oliveira Duarte and the relationship between present, future and past in Fiona Tan’s work Facing Forward; Matthew Mason and the tension between Marxism and post-modernism via Jean-Luc Godard’s La Chinoise; and Riccardo Uras on the absence of debate on Italy’s colonial past and its myths, through the analysis of Adwa: An African Victory by Haile Gerima, and Blood Is Not Fresh Water by Theo Eshetu.